The Karolinska KI/K COVID‐19 immune atlas: An open resource for immunological research and educational purposes. (17th June 2022) - Ljunggren, Hans‐Gustaf; Heggernes Ask, Eivind; Cornillet, Martin; Strunz, Benedikt; Chen, Puran; Rao Muvva, Jagadeeswara; Akber, Mira; Buggert, Marcus; Chambers, Benedict J.; Cuapio Gomez, Angelica; Dzidic, Majda; Filipovic, Iva; et al.
Abstract: The Karolinska KI/K COVID‐19 Immune Atlas project was conceptualized in March 2020 as a part of the academic research response to the developing SARS‐CoV‐2 pandemic. The aim was to rapidly provide a curated dataset covering the acute immune response towards SARS‐CoV‐2 infection in humans, as it occurred during the first wave. The Immune Atlas was built as an open resource for broad research and educational purposes. It contains a presentation of the response evoked by different immune and inflammatory cells in defined naïve patient‐groups as they presented with moderate and severe COVID‐19 disease. The present Resource Article describes how the Karolinska KI/K COVID‐19 Immune Atlas allows scientists, students, and other interested parties to freely explore the nature of the immune response towards human SARS‐CoV‐2 infection in an online setting.